PERBANDINGAN KUAT TEKAN BETON ANTARA CAMPURAN AGGREGAT KASAR BATU PECAH DENGAN AGGREGAT KASAR BATU ALAM PAYAKUMBUH UNTUK BETON STRUKTUR - Masril Masril (Ensiklopedia of Journal, 2020)
The compressive strength of concrete today is strongly influenced by the materials and materials used and is motivated by two types of coarse aggregates and the quality of concrete used for building structures. So as to meet the needs of the current concrete structure. In the selection of concrete material is carried out to determine the strength characteristics of the concrete structure itself, the coarse aggregate material used greatly affects the compressive strength of the concrete. material from coarse aggregates that are used by coarse aggregates of split stones and coarse aggregates of natural stone. In this study comparing the strength of coarse aggregate using split with natural stone (ordinary pebbles) material from Payakumbuh for concrete structures, the implementation of the research was filter analysis, specificity of gross aggregate, and the implementation of Test Slump, each of which was tested on cylindrical test specimens on age 7 days, 14 days, 21 days and 28 days, and the final analysis in this study is the age of 28 days, it turns out that a mixture of coarse aggregate concrete using compressive strength is 264,237 kg / cm² while the rough aggregate consisting of natural stone compressive strength only 246.91 kg / cm ². From the planned quality of the Concrete is K 250 kg / cm ². From the implementation The test differences carried out are suggested for making concrete structures for construction are expected to use split (broken stone) can not use natural stone because strength produced by natural stone is lower than that of Split (broken stone).